Analysis Of The Influence Of Repurchase Intention On Gacoan Noodle Products In Indonesia: - - Damis Veri Budianto; Agus Hermawan; Naswan Suharsono (CV. AFDIFAL MAJU BERKAH, 2024)
Repurchase intent: Repurchase intent is often a step that occurs naturally if a customer has emotions towards a particular product. This research examines the influence of service quality and perceived value on repurchase intentions and customer satisfaction, by considering satisfaction as an intervening variable in the context of Mie Gacoan products. The main objective of this research is to analyze the causal relationship between the independent variable and the dependent variable in the presence of intervening variables. The primary data source in this research is Mie Gacoan customers. Data was collected from a total of 145 customers throughout Indonesia who are Noodle Gacoan connoisseurs. Meanwhile the research method uses a purposive sampling method, while for statistical analysis the PLS 3.0 test tool is used. The majority of Mie Gacoan customers in the sample are women (69%), have a high school/vocational education (51%), are students (49%), and live around one million two hundred thousand rupiah to one million rupiah. rupiah. Eight hundred thousand rupiah (46.9%). The results obtained from this research are as follows: First, perceived value does not contribute to customer satisfaction. Second, service quality contributes to customer satisfaction. Third, satisfaction contributes to repurchase intention. Fourth, service quality contributes to repurchase intention through satisfaction. Fifth, perceived value does not contribute to repurchase intention through satisfaction